Rice farming for climate change adaptation in the Northeastern United States - Chuan Liao; Jenny Kao-Kniffin; Matthew Reid; Wendong Zhang; Precious Tshabalala; Erik Andrus; Zachary Butler-Jones; Jordan LaPoint; Shuai Zhou; Radine Rafols; Seongmin Shin; Mai Ichihara; et al. (Proceedings of the National Academy of Sciences, 2025)
In response to challenges posed by climate change, rice farming emerges as a strategic adaptation in the agriculture sector in the northeastern United States. Cultivating rice can diversify farming practices, create new sources of income, improve water management, and provide habitats for wildlife, enhancing the sustainability of agricultural systems and rural economies. However, challenges such as methane emissions from rice paddies and the risk of metal(loid) contamination highlight the need for adopting best practices in rice cultivation, particularly in land and water management and the selection of suitable rice varieties. By learning from the experience of other temperate rice farming regions and implementing supportive policies, technology, and cooperative frameworks, farming communities in the northeastern United States can learn to navigate these obstacles, ensuring the successful integration of rice farming into its agricultural landscape.